2015
DOI: 10.1038/ki.2015.161
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of acute kidney injury after coronary bypass graft surgery identifies susceptibility loci

Abstract: Acute kidney injury (AKI) is a common, serious complication of cardiac surgery. Since prior studies have supported a genetic basis for postoperative AKI, we conducted a genome-wide association study (GWAS) for AKI following coronary bypass graft (CABG) surgery. The discovery dataset consisted of 873 non-emergent CABG surgery patients with cardiopulmonary bypass (PEGASUS), while a replication dataset had 380 cardiac surgical patients (CATHGEN). Single nucleotide polymorphism (SNP) data were based on Illumina Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 69 publications
0
32
1
Order By: Relevance
“…Low cardiac output and insult may also warrant the use of preoperative intra-aortic balloon pump, which has also been associated with development of postoperative AKI, as suggested by Rosner et al [8] Recently, genetic predisposition to AKI has been studied. Stafford Smith et al conducted an unbiased genome-wide associated study which identified two new loci, namely rs13317787 in GRM7|LMCD1-AS1 intergenic region (3p21.6) and rs10262995 in BBS9 (7p14.3), that increased the risk of AKI following coronary artery bypass grafting (CABG) [10] . The authors also speculated that their findings may become a predictive tool to improve individualised AKI risk stratification in cardiac surgery patients.…”
Section: Introductionmentioning
confidence: 99%
“…Low cardiac output and insult may also warrant the use of preoperative intra-aortic balloon pump, which has also been associated with development of postoperative AKI, as suggested by Rosner et al [8] Recently, genetic predisposition to AKI has been studied. Stafford Smith et al conducted an unbiased genome-wide associated study which identified two new loci, namely rs13317787 in GRM7|LMCD1-AS1 intergenic region (3p21.6) and rs10262995 in BBS9 (7p14.3), that increased the risk of AKI following coronary artery bypass grafting (CABG) [10] . The authors also speculated that their findings may become a predictive tool to improve individualised AKI risk stratification in cardiac surgery patients.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative AKI was defined as a 50% or greater increase or a rise greater than 0.3 mg/dL in serum creatinine within any 48-hour window. 12 …”
Section: Methodsmentioning
confidence: 97%
“…The cohort identified for the current substudy has a limited overlap with participants in prior published analyses involving other postoperative outcomes, some of which reflect more recently enrolled patients. 24-26 …”
Section: Methodsmentioning
confidence: 99%